Green biodiesel production from Jatropha curcas oil using a carbon-based solid acid catalyst: A process optimization study. (April 2023) - Ruatpuia, Joseph V.L.; Changmai, Bishwajit; Pathak, Ayush; Alghamdi, Lana A.; Kress, Thomas; Halder, Gopinath; Wheatley, Andrew E.H.; Rokhum, Samuel Lalthazuala
Abstract: Biodiesel production from low cost, inedible oil represents an increasingly important target for reasons of both sustainability and cost. In this work, we comprehensively verify the batch reproducibility of a sulfonic acid functionalized carbonaceous material (SAFACAM) as catalyst for biodiesel production from inedible feedstock Jatropha curcas oil (JCO). The current catalyst benefits the environment through its atom-efficient, one-pot preparation from an abundant natural biomass derivative (glucose) and has the potential to reduce the overall biodiesel production cost by converting inexpensive raw materials. In this context, JCO has emerged as a crop of interest to the energy sector, potentially providing a reliable and renewable energy source for many countries. Through a central composite design (CCD) approach using response surface methodology (RSM), a 98.7 ± 0.6% conversion of biodiesel is achieved (methanol-to-oil molar ratio 20:1, reaction time 50 min, reaction temperature 120 °C and catalyst loading 9 wt % (with respect to oil)). The chemically satisfactory composition of the biodiesel product has been verified, the reusability of catalyst has been tested, and a significant enhancement in performance when using microwave heating demonstrated. An 83.0 ± 0.8% conversion of JCO is reported in the fifth cycle of reuse. Graphical abstract: Image 1